Design of Smart Walking Shoe for Visually Impaired People - Shelena Soosay Nathan, Shelena Soosay Nathan; Kuan Jung Ying, Kuan Jung Ying; Lim Hui Wen, Lim Hui Wen; Lim Xin Weoi, Lim Xin Weoi (semarak ilmu, 2023)
Technology helps disabled people to get things done easier and in the case of visually impaired people, technology surely enables them to communicate to the surrounding environment independently. The purpose of this study is to propose design of smart walking shoe for the visually impaired people that incorporated with multi sensors. The main purpose of the proposed smart walking shoe is to guide the visually impaired people in a smarter way rather than using traditional method of walking stick. The smart walking shoe is proposed to be integrated with components such as moisture sensor, ultrasonic sensors, button, DF Player and speaker and Agile method will be used in the development process that involves Brainstorm, Design, Development, Quality Assurance and Deployment phase. The pre-evaluation testing shows that the smart walking shoe is shown to be effective as guiding tool to the visually impaired people to navigate independently. The future studies will be conducted by development and tested in actual environments.